Reflexões sobre o não-escolar na escola e para além dela - José Augusto Palhares (Universidade do Minho, 2009)
Assuming that the public school is in a state of transformation, particularly in regard to a (re) definition of its social functions and its expression in structuring the daily lives of children and young people, we commence this reflection nourished by the conviction that it is possible to comprehend it by taking a critical stroll between their borders and at the same time establishing lines of analysis on the relationships that this institution establishes with other educational instances. The implementation of policy measures such as "full time school" appears in this text as a lever to reflective thinking about educational opportunities that may be drafted between the school and the nonschool, both in school space and time and beyond them. We will also discuss the growing centrality of school culture in the construction and definition of pathways, strategies and experiences of education (non-formal and informal) in distinct areas of the life of students.